Pengaruh Keamanan Kerja terhadap Extra-Role Performance dengan In-Role Performance sebagai Variabel Intervening : (Studi pada Petugas Perbatasan Aruk Indonesia-Malaysia, Kabupaten Sambas, Kalimantan Barat) - Desyka Rahman Fitriyani; Silpanus Dian Sapala; Feriansyah, Feriansyah; Eddy Purnomo; Zulimi, Zulimi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The aim of this research is to determine the influence of job security on the extra-role performance of Indonesia-Malaysia border officers in Sebunga Village, Sambas Regency, West Kalimantan with In-Role Performance as an intervening variable. This research is survey research, which uses explanatory research, namely providing an explanation of the causal relationship between variables through hypothesis testing. The sampling technique in this research used a sampling method using saturated sampling or also known as a census, with 50 respondents. Data were analyzed using instrument tests and path analysis. The research results show that each variable has a significant influence even though the influence is not too big. Statistically, Job Security (X) has a direct and significant influence on In-Role Performance. Statistically, In-Role Performance (Z) has a direct and significant influence on Extra-Role Performance (Y). Statistically, Job Security (X) has a direct and significant influence on Extra-Role Performance (Y). Based on statistics, the influence of Job Security (X) is mediated by In-Role Performance (Z) on Extra-Role Performance (Y), proving that In-Role Performance (Z1) is able to mediate the influence of Job Security (X) on Extra-Role Performance (Y).